The social psychology of constructive and destructive social relations - Csepeli, György (Acta Scientiarum Socialium, 2013)
The social psychology of constructive and destructive social relations The paper compares the constructive and destructive social relations with a special emphasize on the human condition engendered by the experience of time. Constructive relations are seen as a force of Good while destructive relations tend to be considered as a force of Evil. Competition, however, is a form of social relations that cannot be categorized easily into neither of the class of constructive or destructive relations. Construction and destruction characterize equally this sort of relations with a huge potential of conflict leading to crisis. Being in crisis social relations enter into chaos.